Design and Analysis of Soybean Epidermis Peeling Machine for Farmers' Group Scale - Rantung, Ruland A.; Tooy, Dedie (ITScience (Information Technology and Science), 2023)
This research aims to design and test a soybean epidermis peeling machine that is cost-effective, efficient, and suitable for small-scale farmers in remote areas. The research process involved designing, manufacturing, and technical testing of the TETA-II model soybean peeler. The data collected during the research was analyzed descriptively. The results showed that the TETA-II model soybean peeler has an average working capacity of 43 kg/hr at an engine speed of 2450-2550 (rpm) with a soybean soaking period of 6 hours. The highest yield from the peeler was achieved at a soybean soaking time of 8 hours (95.955%) and 6 hours (94.02%) at rpm 2450-2550. In future studies about the machine, to improve its efficiency, the scrubber roll system should be adjusted to regulate the stability of the fall of the soybeans being peeled, and the inner walls must be coated with plastic.